Cytokinins and pH on the in vitro culture of strawberry shoots - Durán-Durán, Yutzil; Enríquez del Valle, José Raymundo; Rodríguez-Ortiz, Gerardo; Vásquez-López, Alfonso; Velasco-Velasco, Vicente Arturo (Revista Mexicana de Ciencias Agrícolas, 2026)
Conventional strawberry propagation is performed using runners, which may limit the number and health of plants. The present work assessed the effects of different culture media variants on shoot proliferation in vitro, shoot size and root formation. Seventy-seven variants of culture media were prepared with inorganic salts of the Murashige and Skoog (MS) formulation, different concentrations of two cytokinins, benzylaminopurine, BAP (0, 0.5 and 1 mg L-1) and thidiazuron TDZ (0, 0.5 and 1 mg L-1) and different pH levels (5, 5.5 and 5.8). Data was taken on the number of shoots, the number of leaves and root formation. The data were subjected to analysis of variance and Tukey’s test (0.05). The highest number of shoots (11), with up to 57 leaves, was obtained in the culture medium with 0.5 mg L-1 TDZ, 0 mg L-1 BAP and a pH of 5.5. The lowest numbers of shoots (2.3), with 18 leaves, were obtained in CM without TDZ, 0.5 mg L-1 BAP and a pH of 5.5. In environments with only BAP, the new shoots were taller and formed adventitious roots. TDZ inhibited root formation. It is concluded that the presence of TDZ in CMs stimulated more axillary buds to sprout, while BAP promoted the development of axillary buds but with a lesser effect than that of TDZ.
Keywords: Fragaria x ananassa; benzylaminopurine; shoot proliferation; thidiazuron